2022
DOI: 10.1093/mnras/stac1264
|View full text |Cite
|
Sign up to set email alerts
|

Radio masers on WX UMa: hints of a Neptune-sized planet, or magnetospheric reconnection?

Abstract: The nearby M dwarf WX UMa has recently been detected at radio wavelengths with LOFAR. The combination of its observed brightness temperature and circular polarisation fraction suggests that the emission is generated via the electron-cyclotron maser instability. Two distinct mechanisms have been proposed to power such emission from low-mass stars: either a sub-Alfvénic interaction between the stellar magnetic field and an orbiting planet, or reconnection at the edge of the stellar magnetosphere. In this paper, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 76 publications
(121 reference statements)
3
18
0
Order By: Relevance
“…The V-LoTSS M-dwarf sample is composed of stars at all coronal and chromospheric activity levels, as well as slow and fast rotators (Callingham et al 2021b). In particular, it has been suggested that the highly circularly polarised radio emission from the inactive, slow-rotating M dwarfs in this sample is evidence of a sub-Alfvénic interaction between a star and a putative planet (Vedantham et al 2020b;Callingham et al 2021b;Pope et al 2021;Kavanagh et al 2022). For the more active M dwarfs, the circularly polarised radio emission could be generated by plasma processes or ECMI via the breakdown of co-rotation (Callingham et al 2021a).…”
Section: Galactic Non-degenerate Circularly Polarised Sourcesmentioning
confidence: 82%
See 1 more Smart Citation
“…The V-LoTSS M-dwarf sample is composed of stars at all coronal and chromospheric activity levels, as well as slow and fast rotators (Callingham et al 2021b). In particular, it has been suggested that the highly circularly polarised radio emission from the inactive, slow-rotating M dwarfs in this sample is evidence of a sub-Alfvénic interaction between a star and a putative planet (Vedantham et al 2020b;Callingham et al 2021b;Pope et al 2021;Kavanagh et al 2022). For the more active M dwarfs, the circularly polarised radio emission could be generated by plasma processes or ECMI via the breakdown of co-rotation (Callingham et al 2021a).…”
Section: Galactic Non-degenerate Circularly Polarised Sourcesmentioning
confidence: 82%
“…LoTSS will cover the entire northern sky with an unprecedented root-mean-square (rms) noise of ≈100 µJy beam −1 in full-Stokes polarisation. The unique discovery space that LoTSS provides has already been exemplified by the several studies already published that use preliminary Stokes V data, such as the first direct detection of a brown dwarf from its radio properties (Vedantham et al 2020a), the inference of a star-planet interaction (Vedantham et al 2020b;Kavanagh et al 2022), long-term auroral emission from an active M-dwarf system (Callingham et al 2021a), evidence of closed-field lines extending to large stellar radii around an M-dwarf (Davis et al 2021), new pulsars missed in previous time-domain searches (Sobey et al 2022), and coherent emission detected from chromospherically active binaries (Toet et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The proximity of hot Jupiters to their host stars can potentially cause sub-Alfvénic SPIs, which is expected to produce observable signatures in the stellar atmosphere (e.g., chromospheric emission Ca II H & K line emission; Shkolnik et al 2003Shkolnik et al , 2008Cauley et al 2019) or the planetary atmosphere (e.g., auroral radio emission; Cohen et al 2018;Turnpenney et al 2018;Bastian et al 2022;Kavanagh et al 2021Kavanagh et al , 2022. Such magnetic SPIs in exoplanetary systems were excessively studied by means of magnetohydrodynamic (MHD) simulations (e.g., Preusse et al 2006Preusse et al , 2007Zhilkin & Bisikalo 2020;Varela et al 2018Varela et al , 2022, partly with a focus on the far-field interaction and incorporating self-consistent stellar wind models (e.g., Strugarek et al 2014Strugarek et al , 2019aCohen et al 2011Cohen et al , 2014Vidotto et al 2015;Vidotto & Donati 2017).…”
Section: Introductionmentioning
confidence: 99%
“…chromospheric emission Ca II H & K line emission Shkolnik et al 2003Shkolnik et al , 2008Cauley et al 2019) or the planetary atmosphere (e.g. auroral radio emission Cohen et al 2018;Turnpenney et al 2018;Bastian et al 2022;Kavanagh et al 2021Kavanagh et al , 2022. Such magnetic SPI in exoplanetary systems were excessively studied by means of magnetohydrodynamic simulations (e.g.…”
Section: Introductionmentioning
confidence: 99%